2022
DOI: 10.1186/s12917-021-03120-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carrier solutions on the viability and efficacy of canine adipose-derived mesenchymal stem cells

Abstract: Background Mesenchymal stem cells (MSCs) have favorable characteristics that render them a potent therapeutic tool. We tested the characteristics of MSCs after temporal storage in various carrier solutions, such as 0.9% saline (saline), 5% dextrose solution (DS), heparin in saline, and Hartmann’s solution, all of which are approved by the U.S. Food and Drug Administration (FDA). Phosphate-buffered saline, which does not have FDA approval, was also used as a carrier solution. We aimed to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 84 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…In most of these studies, DMEM growth media was compared to crystalloid solutions ranging from 0.9% saline to PBS to Ringer's lactate and Plasma-Lyte. [26][27][28][29][30][31][32] Specialized storage media examined included HypoThermosol and buffered trehalose solutions. 33,34 With or without the addition of human serum albumin, the maximum duration studied was 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these studies, DMEM growth media was compared to crystalloid solutions ranging from 0.9% saline to PBS to Ringer's lactate and Plasma-Lyte. [26][27][28][29][30][31][32] Specialized storage media examined included HypoThermosol and buffered trehalose solutions. 33,34 With or without the addition of human serum albumin, the maximum duration studied was 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated 4°C storage with a focus on transport. In most of these studies, DMEM growth media was compared to crystalloid solutions ranging from 0.9% saline to PBS to Ringer's lactate and Plasma‐Lyte 26–32 . Specialized storage media examined included HypoThermosol and buffered trehalose solutions 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized three possible causes of poor cell-delivery efficiency during intravenous infusion: (1) acute cell death due to nutrient deprivation and hypoxic stress in the suspension solution or biomechanical stress during infusion; (2) cell adhesion to the walls of the apparatus, such as the infusion bag, syringe, or infusion tube; and (3) cell aggregation during storage and infusion. Temperature, solution type, and cell density of the cell preparation, as well as storage, can affect the metabolic activity of MSC, thus altering their viability and function [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. It has been reported that the viability of hADSC in NS is better maintained at lower temperatures (4 °C) than at room temperature (37 °C) [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suspension in DEX appeared to cause cell bursting and an increase in dead cells. Pal et al reported that DEX was suitable for preserving hBMSC [ 45 ], but similar studies with hUCMSC [ 46 ], hADSC [ 47 ], and cADSC [ 48 ] reported low viability with this solution. The mechanism responsible for the decreased viability is unknown, but may be related to factors other than pH or osmotic pressure [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saline solution and 5%DS were able to maintain optimal viability and colony forming units ability up to 12hrs. Gene expression levels of CD105 and CD90 reached significantly higher expression in cells stored in PBS, while collagen type II alpha 1 chain (COL2A) and SRY-Box Transcription Factor 9 (Sox 9) were highly expressed in chondrogenically-differentiated MSCs that had been stored respectively in saline and HS (209). Based on this, it is important to carefully consider and test various cell carriers by testing their efficacy and stability on the final product of the manufacturing process.…”
Section: Transport and Cell Deliverymentioning
confidence: 99%